2022
DOI: 10.15252/embr.202153600
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus NS1 protein conveys pro‐inflammatory signals by docking onto high‐density lipoproteins

Abstract: The dengue virus nonstructural protein 1 (NS1) is a secreted virulence factor that modulates complement, activates immune cells and alters endothelial barriers. The molecular basis of these events remains incompletely understood. Here we describe a functional high affinity complex formed between NS1 and human high‐density lipoproteins (HDL). Collapse of the soluble NS1 hexamer upon binding to the lipoprotein particle leads to the anchoring of amphipathic NS1 dimeric subunits into the HDL outer layer. The stabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
46
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 87 publications
8
46
1
Order By: Relevance
“…This is similar to our structure of 5E3 complexed with NS1 dimeric obtained after Fab 5E3 has dismantled the loose tetramer and hexameric sNS1 structures. Both Benfrid et al 23 and Chew et al 27 did not show any high-resolution structures of sNS1 complexed with HDL, likely because their samples might be very heterogeneous and/or flexible, thus complicating cryoEM structural determination. Thus our cryoEM study shows the sNS1 structures before it is complexed with any host proteins.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…This is similar to our structure of 5E3 complexed with NS1 dimeric obtained after Fab 5E3 has dismantled the loose tetramer and hexameric sNS1 structures. Both Benfrid et al 23 and Chew et al 27 did not show any high-resolution structures of sNS1 complexed with HDL, likely because their samples might be very heterogeneous and/or flexible, thus complicating cryoEM structural determination. Thus our cryoEM study shows the sNS1 structures before it is complexed with any host proteins.…”
Section: Discussionmentioning
confidence: 92%
“…Benfrid et al 23 also showed that sNS1 it binds to low-density lipoproteins, albeit with lower affinity. Benfrid et al 23 reported negative-stain EM 2D class averages of the purified sNS1:HDL complex containing heterogeneous particles with either two, three, and four NS1 dimers on the HDL surface. They suggested how a hexameric sNS1 could rearrange into three dimers on the HDL surface.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations